Corporate social responsibility in business practices of multinational companies: study of differences between Czech and Slovak - Skýpalová, Renata; Kozáková, Jana; Urbánová, Mária; Di Sabato, Vito (Business, Management and Economics Engineering, 2023)
Purpose – find differences in the core principles of implementation of CSR (Corporate Social Responsibility) practices in subsidiaries of foreign multinationals in Slovak and Czech Republic, two similar yet different countries.Research methodology – the questionnaire was distributed to local daughter companies of foreign multinational enterprises selected on the basis of stratified randomization. The sample: 360 enterprises (180 from each country). Mann‐Whitney U Test was used for the analysis (non-normally distributed data) of the differences between Slovak and Czech companies in their CSR implementation.Findings – differences among the two countries in the implementation of CSR exist in few factors due to their joint history.Research limitations – the representativeness of companies connected with foreign mother companies in the two countries cannot be computed: no data are available. To overcome this issue, the same number of monitored entities was analysed to so as to make further statistical analysis possible.Practical implications – the results can be used by business entities, which may benefit from comparing themselves against other players on the market or against the average situation on the monitored markets. Moreover, teaching future managers and promoters CSR is of significant importance.Originality/Value – the work sheds lights on CSR practices in Czechia and Slovakia, two countries in which there is a lack of studies on the topic of CSR.